Rapid quantification and validation of etomidate and dexmedetomidine blood concentrations in rats using a novel portable mass spectrometer - Liu, Sicheng; Li, Xiaoxiao; Gong, Deying; Huang, Yanhua; Zhang, Wensheng (Frontiers in Veterinary Science, 2025)
In clinical anesthesia, precise dosing depends on feedback from blood drug concentrations. However, rapid tools for measuring these concentrations are currently limited. This study evaluated the capability of a novel portable mass spectrometer (CELL) to rapidly quantify etomidate and dexmedetomidine in rat plasma. The 50% effective dose (ED50) of both drugs was determined using the up-and-down method. CELL's methodology was validated according to standard guidelines. Linear regression and intraclass correlation coefficient (ICC) analyses were conducted to assess the consistency between CELL and HPLC-MS measurements. The ED50 of etomidate was found to be 0.9 mg/kg and that of dexmedetomidine was 21.1 μg/kg in rats. For etomidate, CELL demonstrated linearity in the range of 210–2,000 ng/ml (y = 427.0x – 30,526, R2 = 0.995) with a limit of quantitation (LOQ) of 210 ng/ml. For dexmedetomidine, linearity was observed in the range of 6–1,000 ng/ml (y = 14,669x + 109,875, R2 = 0.997) with an LOQ of 6 ng/ml. In the mixed group, etomidate showed linearity in the range of 100–2,000 ng/ml (y = 431.4x + 11,864, R2 = 0.996) with an LOQ of 100 ng/ml, while dexmedetomidine exhibited linearity in the range of 5–1,000 ng/ml (y = 14,141x + 52,430, R2 = 0.997) with an LOQ of 5 ng/ml. A strong linear correlation was observed between CELL and HPLC-MS. These results indicate that CELL provides excellent performance in the rapid and simultaneous quantification of both drugs, supporting real-time monitoring to meet diverse clinical requirements. This approach has strong potential for point-of-care (POC) monitoring in perioperative veterinary and human anesthesia.